Peningkatan Hasil Belajar Ips Melalui Pembelajaran Numbered Heads Together (Nht) Kelas IV SD Gmim 7 Tomohon - Hetty J. Tumurang (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is a classroom action research that aims to improve social studies learning outcomes at GMIM VII Tomohon Elementary School. The implementation of this research consists of four stages, namely planning, implementation, observation and evaluation and reflection. The subjects in this study were the fourth grade students of GMIM VII Tomohon Elementary School as many as 27 people, 14 male students and 13 female students. Data on the results of students' understanding of the social studies subject matter of natural appearances and socio-cultural diversity through the provision of tests at the end of the cycle. Data on student activity during the learning process is obtained from the results of observations filled in on the observation sheet. The data obtained from the observations were analyzed qualitatively while the data on the results of the sociology study were analyzed quantitatively. The results showed that in the first cycle which was completed individually from 27 students, only 11 students or 40.7% met the minimum completeness criteria. Classically it has not been fulfilled because the average value obtained is 58.7. Whereas in the second cycle, 26 students or 96.7% have met the minimum completeness criteria and classically have been fulfilled, namely the average value obtained is 75.9. In the first cycle student learning outcomes are in the medium category. This means that student learning outcomes on the subject matter increased from the medium to high category. Based on the results of the research above, it can be concluded that the social studies learning outcomes of elementary school students GMIM VII Tomohon through the application of the Numbered Heads Toghether learning model have increased